2008
DOI: 10.3928/00989134-20080901-05
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of The Geriatric Oral Health Assessment Index in Turkey

Abstract: The purpose of this study was to test the reliability and validity of the Turkish version of the Geriatric Oral Health Assessment Index (GOHAI). Data were obtained from a cross-sectional survey of 101 older adults living at a residential home in the Izmir municipality of Turkey. The Turkish version of the GOHAI showed acceptable reliability and validity. The Cronbach's alpha coefficient was 0.75, and item-scale (Pearson's) correlations varied between 0.30 and 0.67. Low GOHAI scores were associated with perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 20 publications
6
40
2
1
Order By: Relevance
“…Furthermore, the level of education or the place of residence often correlates with GOHAI scores [8, 43, 58], but for schizophrenic patients, we found no significant differences. In our study, several clinical measurements were related to the GOHAI score, indicating that the perception of the patients about their oral health was clearly associated with their objective dental status.…”
Section: Discussioncontrasting
confidence: 73%
“…Furthermore, the level of education or the place of residence often correlates with GOHAI scores [8, 43, 58], but for schizophrenic patients, we found no significant differences. In our study, several clinical measurements were related to the GOHAI score, indicating that the perception of the patients about their oral health was clearly associated with their objective dental status.…”
Section: Discussioncontrasting
confidence: 73%
“…Other studies have also found, that demographic factors have been associated with higher QOL; included age, gender and income. [23][24][25] In the present study we reported a significant relationship of physical and psychological domain and educational level. These results are in good agreement with findings in the history of public health research, in that the lower socioeconomic strata are associated with lower health status.…”
Section: Discussionsupporting
confidence: 56%
“…This study was conducted on 417 elderly subjects. Apart from China study, sample of other similar studies ranged from 101 to 288 people,,,. The Persian version of GOHAI showed reasonable reliability among Persian elders.…”
Section: Discussionmentioning
confidence: 89%
“…The GOHAI has been also found to be a significant predictor of self‐rated dental appearance among older people. Its internal consistency was satisfactory in a number of countries including China, Malaysia, Sweden, Germany, France, Turkey, Romani, Japan, India and some Arab countries, where local versions have shown acceptable reliability,.…”
Section: Introductionmentioning
confidence: 98%